The Role Of Spiritual Intelligence Of Students In Mathematical Learning - Imamuddin, M.; Isnaniah, Isnaniah; Ismail, Ismail (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
One of the students' accomplishments in learning is influenced by internal factors. Spiritual intelligence is one of the aspects that can impact students’ achievement. Students’ spiritual intelligence is varied. This is a literature review research. The aim of this study is to find out the role of students' spiritual intelligence in learning mathematics. The data collected in the form of data obtained from articles and proceedings taken from the best Google scholar web. Data collection was carried out by going through the stages of planning, searching for articles, and documentation. Based on the data, the researcher then conducted tabulation and in-depth analysis of the collected data. Finally, based on the steps that have been determined, the researcher got the result. The results of the research regarding the role of students' spiritual intelligence in learning mathematics are: 1) students' spiritual intelligence can influence students' motivation to learn mathematics, higher spiritual intelligence will result higher motivation to learn mathematics, 2) higher spiritual intelligence will affect lower students' mathematics anxiety, 3) there is a linear relationship between students' spiritual intelligence and literacy abilities, 4) higher the spiritual intelligence will result higher students' mathematical problem solving abilities, and 5) higher spiritual intelligence will result higher achievement/study of mathematics students